Why Governments Devolve: A Study Using Data from Indian States - Sanjay Mitra and Shashi Kant Verma (Development Discussion Paper No. 586, 1997)
Recent studies have focused upon the role of devolution of financial and administrative authority to local governments. It is generally believed that devolution leads to better implementation of public projects and programs, and to improvements in the quality of governance and democratic participation. This paper seeks to establish a simple methodology to explore the determinants of devolution and thereafter to broadly examine its impact on government policies. Using data from the states of India, we show that the extent of devolution is determined by the extent of caste or communal diversity in a state, the stability and the policy orientation of the ruling political party at the state level, and, most importantly, the prevailing attitude of its political and bureaucratic elite towards the delegation of financial and administrative authority. We show that greater devolution helps in containing those expenditures of the state government that are purely administrative in nature. A higher degree of devolution also enhances the extent of electoral participation, stimulates productive economic behavior measured in terms of greater agricultural output and increases the demand for social services. We conclude that devolution can be largely explained by political and institutional factors. Economic factors play a relatively smaller role. We suggest that devolution represents the degree of internal openness of the political and economic system., analogous to the concept of external openness used in development literature.